Hot tearing and mechanical properties of high electrical and thermal conductivity Al-Fe-Mg-Si-Ni Alloys. (2nd November 2022) - Kotiadis, Stephanie; Zimmer, Adam; Elsayed, Abdallah
ABSTRACT: Aluminium alloys with Fe and Ni show potential as high castability alloys with high strength and high electrical/thermal conductivities for electric vehicle powertrains. Permanent mould castings of Al-Fe-Ni alloys with additions of Mg and Si were prepared to assess hot tearing susceptibility and mechanical properties. The electrical conductivity of the Al-Fe-Ni alloys was measured, and the Wiedemann-Franz law was used to estimate the thermal conductivity. The results show that a hot tear resistant Al-Fe-Ni alloy with composition Al-1.2Fe-0.5Mg-0.3Si-0.2Ni had an electrical conductivity of 50.91 ±0.29%IACS with yield strength, ultimate tensile strength, and elongation of 60.5 MPa, 141 MPa and 7.9%, respectively. The microstructure of the Al-Fe-Ni alloys contained primary Al, Al9 FeNi and Mg2 Si. The short freezing ranges and fine intermetallics allowed for good castability. The prepared Al-Fe-Ni alloys are potential new castable Al alloys that have thermal and electrical conductivity nearing wrought (6061 and 6101) compositions.